2011
DOI: 10.3727/096368910x550189
|View full text |Cite
|
Sign up to set email alerts
|

Local Transplantation of G-CSF-Mobilized CD34+Cells in a Patient with Tibial Nonunion: A Case Report

Abstract: Although implantation of crude bone marrow cells has been applied in a small number of patients for fracture healing, transplantation of peripheral blood CD34(+) cells, the hematopoietic/endothelial progenitor cell-enriched population, in patients with fracture has never been reported. Here, we report the first case of tibial nonunion receiving autologous, granulocyte colony stimulating factor mobilized CD34(+) cells accompanied with autologous bone grafting. No serious adverse event occurred, and the novel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 29 publications
(34 reference statements)
1
31
0
Order By: Relevance
“…As a pilot case from a phase I/IIA clinical trial, Kuroda et al [41] reported the results of transplantation of autologous peripheral blood CD34? cells, the hematopoietic/EPCenriched population, in a patient with non-union of a tibia fracture.…”
Section: Future Perspectives and Clinical Rationalementioning
confidence: 98%
“…As a pilot case from a phase I/IIA clinical trial, Kuroda et al [41] reported the results of transplantation of autologous peripheral blood CD34? cells, the hematopoietic/EPCenriched population, in a patient with non-union of a tibia fracture.…”
Section: Future Perspectives and Clinical Rationalementioning
confidence: 98%
“…More than 10 clinical trials [4][5][6][8][9][10][11][12][13][14] have been performed to elucidate the therapeutic effects of EPCs. These studies have provided information regarding the feasibility of using EPCsbased therapy to promote vasculogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Kocher, et al 7) infused freshly isolated human EPCs into a nude rat model of myocardial ischemia and observed preservation of left ventricular (LV) function and inhibition of cardiac apoptosis. More than 10 clinical trials [4][5][6][8][9][10][11][12][13][14] have been performed to elucidate the therapeutic effects of EPCs. These studies have provided information regarding the feasibility of using EPCsbased therapy to promote vasculogenesis.…”
Section: N the Last Decade Several Types Of Cells Have Been Utilizedmentioning
confidence: 99%
“…Fixation methods included fixation with autologous bone grafting (n=78), fixation revision (n=8), autologous bone grafting without fixation revision (n=7), en bloc resection of the infected bone at the first stage and reconstruction using bone lengthening at the second stage (n=2), and transplantation of peripheral blood CD34-positive cells 14 and autologous bone grafting (n=7). Bone substitute or bone morphogenetic protein was not used.…”
Section: Methodsmentioning
confidence: 99%